Solving recurrence relations supported by Wolfram Mathematica - Vílchez-Quesada, Enrique (2015)
This paper introduces some algorithms for solving linear relationships, homogeneous and non-homogeneous recurrence with constant and non-constant coefficients, using software as the main resource in solving processes. The Mathematica commercial application has provided the technical support necessary for the implementation of the methods used. It also presents other examples of recurrence relations, showing the effectiveness and limitations of the algorithms created by the author and programmed in Mathematica environment that provides.